(untitled) (Journal of Universal Science Research, 2023)
The concept of adolescence is relatively new, having only been recognized in the United States starting in the late nineteenth century. Previously, adolescents were essentially seen as "miniature adults." However, we currently understand that development continues throughout the lifespan, meaning that teenagers are different from adults developmentally. Specifically, decades of research have shown that adolescents undergo significant brain development, impacting their behavior and functioning during this phase.